Reaching SDGs through climate change mitigation - Yomayuza Herrera, Karoll Valentina (2024)
Descripción: Climate change impacts go beyond emissions; they intertwine with sustainable development and well-being. This video explores how addressing climate change can help achieve up to 80% of the Sustainable Development Goals (SDGs). The Low-Emission Food Systems team discusses the challenges and opportunities in aligning climate action with goals like poverty eradication, food security, and biodiversity conservation. Learn how strategic planning and co-benefits can build a sustainable future for all.